PENGGUNAAN MULTIMEDIA DALAM PEMBELAJARAN BAHASA SASTRA INDONESIA DI SMP NEGERI 2 BAWEN KABUPATEN SEMARANG - RUSMIYATI, IDA (Jurnal Teknologi Pendidikan dan Pembelajaran, 2014)
The purpose of this research are: (1) to know about usage of multimedia in Indonesian Language and Literature Learning; (2) to know about the positive impact of multimedia usage toward the quality and progress of learning Indonesian Language and Literature; (3) to understand the supporting and resisting factors of the usage of multimedia in Indonesian Language and Literature Learning.This is a qualitative research.Â  The data analysis uses interactive analysis model. The results of the research show that: (1) the usage of multimedia in Indonesian Language and Literature learning was conducted with a complete planning. The teacher prepared the curriculum such as Syllabus, Lesson Plan (RPP), assessment instrument, material, Media, LCD, and also laptop. The Multimedia was used by the teacher as a medium to give motivation at the beginning of the activity in front of the class. (2) The multimedia has positive impact toward the learning quality. The quality improvement can be seen from the increase of motivation, enthusiasm, and also the studentsâ understanding. (3) The supporting factor of the multimedia usage in Indonesian language and literature learning comes from the complete facilities and infrastructures, the good competence of the teacher in using and managing the class, good understanding of the students, and the availability of learning sources. Whereas the resisting factors found are the lack of funds, the absence of radiator machine and the reduced time in consequence of the teacherâs necessity to leave the class for official and private interests.Â Keywords: learning, multimedia, language literature, Indonesian